PUBLIC FINANCIAL POLICY IN THE SPHERE OF LOANS IMPLEMENTATION AND DEBT MANAGEMENT - M. Sverdan (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Investigate questions of public borrowing, advanced features of the formation of public debt and its management. An assessment of the structure of public debt and the likelihood of debt risk state. Justified by current policy priorities of government borrowing and public debt service.